Effects of Multimodal Learning Analytics with Concept Maps on College Students’ Vocabulary and Reading Performance - Shih-Ping Wang; Yih-Lan Chen (Educational Technology & Society, 2018)
This study integrated the multimodal framework of learning analytics (IMFLA) with the concept mapping (Cmap) approach to improve students’ vocabulary and reading abilities. A total of 70 participants were divided into 2 classes, Class 1 (experimental) and Class 2 (control), for a 1-year period. Vocabulary and reading tests were implemented 3 times. Repeated measures were conducted to test the effect of the program. The results indicated that Time had a significant effect on enhancing both outcome measures (p < .01 for vocabulary; p < .001 for reading). Moreover, significant interaction effects between Time and the program on both vocabulary (p < .05) and reading (p < .001) further suggest that a longer period of time spent on the program would result in a significant effect on both the vocabulary and reading outcome measures. That is, a significant interaction effect occurred between IMFLA and the time factor. Such interaction effects resulted in better vocabulary and reading abilities when students of Class 1 spent more time on the IMFLA procedure. The multimodal and learning analyses of students’ weekly logs confirmed this improvement. We therefore suggest that instructors use digitalized wordlists and Cmaps in language instruction to enhance students’ vocabulary and reading abilities.